2012
DOI: 10.1002/ibd.21896
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab for the Treatment of Active Ulcerative Colitis: A Randomized Controlled Phase 2 Dose-ranging Study

Abstract: Vedolizumab demonstrated dose-proportional pharmacokinetics and maximally saturated α(4) β(7) receptors over the tested dose range. Multiple dosing up to 10 mg/kg was well tolerated. Over the course of follow-up a greater proportion of patients treated with vedolizumab were in clinical response than those who were assigned to placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
197
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(213 citation statements)
references
References 23 publications
13
197
0
3
Order By: Relevance
“…The large GEMINI 1 trial [16] reported the most common adverse effects included an exacerbation of colitis, headache and nasopharyngitis. A similar set of adverse effects were reported by Parikh et al [15] However, overall the frequency for which these events occur are uncommon. Certainly Parikh et al [15] reported no withdrawal from their clinical trial as a consequence of adverse effects.…”
Section: Adverse Effectssupporting
confidence: 73%
See 3 more Smart Citations
“…The large GEMINI 1 trial [16] reported the most common adverse effects included an exacerbation of colitis, headache and nasopharyngitis. A similar set of adverse effects were reported by Parikh et al [15] However, overall the frequency for which these events occur are uncommon. Certainly Parikh et al [15] reported no withdrawal from their clinical trial as a consequence of adverse effects.…”
Section: Adverse Effectssupporting
confidence: 73%
“…A similar set of adverse effects were reported by Parikh et al [15] However, overall the frequency for which these events occur are uncommon. Certainly Parikh et al [15] reported no withdrawal from their clinical trial as a consequence of adverse effects. The concern regarding PML has also not proven to be of significance [15,16] .…”
Section: Adverse Effectssupporting
confidence: 73%
See 2 more Smart Citations
“…Antibody natalizumab to ␣ 4 is approved for Crohn disease (43), and vedolizumab specific for ␣ 4 ␤ 7 is advancing in human trials (44). Targeting MAdCAM is an alternative and highly specific method of treating inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%